Improving ternary blend morphology by adding a conjugated molecule into non-fullerene polymer solar cells. Issue 71 (9th December 2020) - Zhao, Di; Jia, Pengcheng; Li, Ling; Tang, Yang; Cui, Qiuhong; Zhan, Chuanlang; Hou, Yanbing; Hu, Yufeng; Lou, Zhidong; Teng, Feng
Abstract : The use of ternary polymer solar cells (PSCs) is a promising strategy to enhance photovoltaic performance while improving the fill factor (FF) of a device, but is still a challenge due to the complicated morphology. Abstract : The use of ternary polymer solar cells (PSCs) is a promising strategy to enhance photovoltaic performance while improving the fill factor (FF) of a device, but is still a challenge due to the complicated morphology. Herein, ternary PSCs are fabricated via adding the conjugated small molecule p -DTS(FBTTh2 )2 into a well-known blended film, PTB7-Th :IEICO-4F . The ternary blend morphology and device characterization reveal that the addition of p -DTS(FBTTh2 )2 can improve crystallinity and optimize morphology, leading to the FF of the optimized device increasing to 73.69%. In combination with the advantages of an ultra-narrow bandgap material, IEICO-4F, with a broad optical absorption spectrum, the optimized ternary solar cell exhibits a high short-circuit current–density ( J SC ) of 25.22 mA cm −2 . The best power conversion efficiency (PCE) is 12.84% for this optimized ternary device with 10 wt% p -DTS(FBTTh2 )2 in the donors. This work indicates that incorporating a small molecule with high crystallinity into host binary non-fullerene PSCs would give an active layer with high crystallinity, thus greatly enhancing the FFs and PCEs of PSCs.